The role of electronic administration in devoting administrative transparency and fighting administrative and financial Corruption - Mezhoud, El Hachemi; Rabahi, Moustafa (Journal of Human Sciences, 2020)
Electronic administration is considered a new administrative method in line with the developments of digital technology. Its application in administrative work has achieved important advantages in terms of management efficiency. Administrative and financial facilities for public utilities, and digitization can also contribute to efforts of fighting administrative and financial corruption through the transparency and accuracy of the data it provides Facilitating the work of the mechanisms for controlling public money, public officials and employees, The digitization of the country’s public finances and the tax and accounting departments has a prominent role in this, In addition to setting up information systems at the level of the departments in charge of contracting in Public deals and administrative administration of the large public expenditures involved in both operations And the overlap of several sides in the..